THE QUALITY OF PUBLIC SERVICES IN THE PURWANEGARA VILLAGE OFFICE, NORTH PURWOKERTO SUB-DISTRICT, BANYUMAS REGENCY - Ganesa Eka Suswanti; Andri Trianfano; Oti Kusumaningsih (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
This research is entitled